Active and Passive Seismic Imaging of the Central Abitibi Greenstone Belt, Larder Lake, Ontario. Issue 2 (9th February 2022) - Naghizadeh, Mostafa; Smith, Richard; Rubingh, Kate; Sherlock, Ross; Ayer, John; Lafrance, Bruno; Cheraghi, Saeid; Snyder, David; Vergne, Jérome; Hollis, Dan; Mordret, Aurélien
Abstract: Passive seismic methods are considered cost‐effective and environmentally friendly alternatives to active (reflection) seismic methods. We have acquired colocated active and passive seismic surveys over a metal‐endowed Archean granite‐greenstone terrane in the Larder Lake area to investigate the reliability of estimated elastic properties using passive seismic methods. The passive seismic data were processed using two different data processing approaches, ambient noise surface‐wave tomography (ANSWT) and receiver function analysis, to generate shear‐wave velocity and P to S wave ( P ‐ S ) convertibility profiles of the subsurface, respectively. The Cadillac‐Larder Lake Fault (CLLF) was imaged as a south‐dipping subvertical zone of weak reflectivity in the reflection seismic profile. To the north of the CLLF, a package of north‐dipping reflections in the upper crust (at depths of 5–10 km) resides on the boundary of high (on the top) and low (on the bottom) shear‐wave velocity zones estimated using the ANSWT method. This package of reflections is most likely caused by overlaying mafic volcanic and underlying felsic intrusive rocks. The P ‐ S convertibility profile imaged the Moho boundary at ∼40‐km depth as well as a south‐dipping feature that penetrates the mantle, which is interpreted to be either caused by the delamination of the lower crust or a possible deeper extension of the Porcupine‐Destor Fault. Overall, the reflectivity, shear‐wave velocity, and P ‐ S convertibility profiles exhibit a good correlation and provided a detailed image of the subsurface lithological structure to a depth of 10 km. Plain Language Summary: It is becoming increasingly important to conduct mineral exploration projects in an environmentally friendly manner with minimal footprints left behind on the natural landscapes. Active source seismic reflection methods are considered the most accurate subsurface imaging geophysical prospecting methods; however, they often have high acquisition costs and might cause significant alterations to the environment. Passive seismic methods that utilize natural seismic sources can overcome most of these challenges. However, benchmark studies are still required to validate the effectiveness and accuracy of the images produced by passive seismic methods. We have conducted such a study by acquiring active and passive seismic surveys along an ∼40‐km transect in a world‐class gold mineralization zone in Larder Lake, Ontario, Canada. Passive seismic records provided a map of surface‐wave (similar to ocean waves) speeds by using everyday environmental seismic noise as well as mapping locations at depth of rock layers that convert seismic P and S waves from distant earthquakes. The good correlation between the active and passive seismic results indicated that properly designed passive seismic surveys can be used as alternatives to active seismic surveys, leading to cheaper acquisition costs and fewer disturbances to the environment and nature. Key Points: We acquired active and passive seismic surveys over a metal‐endowed region to investigate the reliability of passive seismic methods The seismic reflectivity, shear‐wave velocity, and P ‐ S convertibility profiles exhibited a very good correlation and were complementary This study provided detailed geophysical models of the upper crust (top 10 km) and upper mantel (beneath the Moho) in the central Abitibi